2016
DOI: 10.1002/cb.1564
|View full text |Cite
|
Sign up to set email alerts
|

The interplay of persuasion inference and flow experience in an entertaining food advergame

Abstract: Increasingly, unhealthy food is being advertised through online games known as advergames. The advergame is designed for entertaining fun to promote the brand featured in the game. But what happens if the food advertised is healthy or the source of the game is non‐commercial? This study examines how people's entertainment (flow experience) interacts with their inference about the persuasion impact of food brands featured in an advergame, which vary according to their persuasion knowledge about the source (e.g.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
41
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(46 citation statements)
references
References 57 publications
4
41
0
1
Order By: Relevance
“…Marketing research has found games can persuade player's preferences toward brands (Kuo & Rice, ; Waiguny, Nelson, & Terlutter, ) and increase intentions to perform behaviors (Ham, Yoon, & Nelson, ). One recent study by Ham and colleagues () found that advergames (a game which incorporates a product or brand) can encourage players to purchase healthy food brands and products. It, therefore, appears that there is both support in the gaming and marketing literature for games to have a persuasive role in creating socially responsible behaviors.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Marketing research has found games can persuade player's preferences toward brands (Kuo & Rice, ; Waiguny, Nelson, & Terlutter, ) and increase intentions to perform behaviors (Ham, Yoon, & Nelson, ). One recent study by Ham and colleagues () found that advergames (a game which incorporates a product or brand) can encourage players to purchase healthy food brands and products. It, therefore, appears that there is both support in the gaming and marketing literature for games to have a persuasive role in creating socially responsible behaviors.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Multiple studies have set to determine the specific age thresholds when children start processing advertisements critically, supposedly becoming less susceptible to persuasive messages (Boush, Friestad, & Rose, ; P. J. Kelly, ; McAlister & Cornwell, ; Robertson & Rossiter, ; Rozendaal, Buijzen, & Valkenburg, ). This branch of research was later followed by studies about children's application of their advertising knowledge (see Ham, Nelson, & Das, ; Ham, Yoon, & Nelson, ; Vanwesenbeeck, Ponnet, & Walrave, ; Vanwesenbeeck, Walrave, & Ponnet, ).…”
Section: Introductionmentioning
confidence: 99%
“…The observed attitudinal (Rifon et al ., ; van Reijmersdal et al ., , ) and behavioral brand outcomes (Dias and Agante, ; Harris et al ., ; Hernandez and Chapa, ; Mallinckrodt and Mizerski, ; Rifon et al ., ; van Reijmersdal et al ., ) are in line with the existing literature on advergame effects. However, the existing studies on advergame effects on children have predominantly focused on electronic games promoting food or beverages (Ham et al ., ; Dias and Agante, ; Harris et al ., ; Mallinckrodt and Mizerski, ; Rifon et al ., ). Hence, they mostly focused on the outcomes of embedded advertising techniques on child‐specific or child‐relevant products.…”
Section: Discussionmentioning
confidence: 98%
“…One relatively new form of reaching out to children in a very playful and entertaining manner is the so‐called “advergame” (Terlutter and Capella, ). The existing studies on advergame effects on children have predominantly focused on electronic games promoting food or beverages (Choi et al ., ; Dias and Agante, ; Ham et al ., ; Harris et al ., ; Hudders et al ., ; Mallinckrodt and Mizerski, ; Rifon et al ., ). These studies primarily investigated the evaluation of brands or products that are used and consumed by children in their daily life.…”
mentioning
confidence: 98%